Visitors in the land : values, opinions and perceptions of visitors to inform management at seal watching spots in Northwestern Iceland - Chauvat, Cécile Marie, 1996- (2020)
Verkefnið er lokað til 15.06.2021. Tourism has increased in Iceland and wildlife tourism is a popular activity. Previous research shows that tourism pressure may lead seals to change their spatial distribution or to be more vigilant, indicating that tourism may disturb the critically endangered population of harbor seals in Iceland. The aim of this study was to investigate how best to manage visitors along the Vatnsnes peninsula in Húnaþing vestra to limit tourists’ impacts on sensitive seal species in Iceland. The objectives were to investigate what types of management actions would be accepted most easily, and if there are differences in acceptance of regulations or awareness of the impacts of seal watching depending on visitors’ level of egoistic and biospheric values. A person’s values act as guiding principles throughout their life; and biospheric and egoistic values determine to what degree a person makes decisions based on their impact on the environment or their own well-being. Visitor surveys were collected at two seal watching spots and a seal museum (n=597). This study finds that seal watching visitors have high biospheric values, low egoistic values, and are open to most regulations. High biospheric values are correlated with acceptance of management actions, and high egoistic values are correlated with low acceptance of management actions and low awareness of the impacts of seal watching. These results will inform managers on which management actions may be the most effective to encourage ethical behavior at seal watching sites and help them in designing a management strategy for Icelandic seal watching.